SIMILARITIES OF FOOD-RELATED PHRASES IN CHINESE AND UZBEKISTAN DISCOURSE - Nosirova Mohira Kobiljon kizi (Web of Journals Publishing, 2025)
The mutual cooperation between the peoples of Uzbekistan and China has historical foundations and dates back to the era of the Great Silk Road. Therefore, to this day, many similarities can be seen in the lives and traditions of our peoples. This article discusses the similarities of expressions related to food in Chinese and Uzbek discourse.
Keywords: China, Uzbek, food, similarity, expressions.